desertification process altoandina olleros district area (Huaraz, ancash) - Cruz Reyes, Fray Masias (2013)
The territory of Olleros district is considered high Andean, and extends from 3600 masl. Olleros bounded on the east by the Cordillera Blanca, so the entire territory corresponde to the western side of this, which is characterized by steep slopes over 20% of its length. Being a very rugged territory because of the steady flow of water from the numerous ravines or talwegs (in this case: Mashuan, Aco, Arzobispo, Puyhuan, Rurec and Arhuey), there can be distinguished four natural regions: Quechua, Suni, Jalca and Puna. Regions where the vegetation dominated is mainly short-stemmed and herbaceous temporary ,also with predominantly Ichu Stipa and Andean trees as Quinual (Polylepis incana) at Quebrada Rurec in inaccessible areas and high altitude (4600 m) and the Quisuar (Buddleia coreacea). The process of desertification in this part of the territory is very intense due to the practice of agricultural and livestock activities. Adding to this the geographical characteristics of the territory, there are strong surface runoff during rainy seasons, producing intense soil erosion by the sharp gradients of the terrain and low vegetation cover. The desertification process results in soil erosion and loss of capacity agrological by natural causes and human activity (manifested in the intensive land use for agriculture and livestock). Human activities practice without technology or knowledge necessary to avoid worsening the situation of the soils are some of the major causes of desertification problem affecting the population, generating low productivity of economic activities, loss of farming areas, and the consequent depopulation and population migration to cities.